SUPERVISI KINERJA KEPALA SEKOLAH DI SDN UPT KECAMATAN BATANG GASAN KABUPATEN PADANG PARIAMAN - Nofriza Efendi (Bajang Institute, 2022)
This study aims to describe the supervision of the performance evaluation of school principals in cluster 1 in primary school Batang Gasan, Padang Pariaman District. The approach used is a descriptive qualitative approach by describing supervision of the principal's performance in the learning process. Data collection techniques used were observation and interviews with a total of 8 principals. The results showed 60% of school principals as supervisors were very successful in conducting supervision activities with many changes that occurred in the school.